Pengaruh Layanan Food delivery O2O (Online to Offline) Terhadap Keputusan Pembelian dengan Electronic Word of Mouth (E-WOM) Sebagai Variabel Dummy - Hestika Dwi Mukti; Febrina Hambalah (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2022)
The advanced technology is one of the reasons to create an easy beverage transaction through online system and to get information from social media, such as Electronic Word of Mouth (E-WOM) and Food delivery service platform (O2O). Thai Tea beverage business “nyot-nyot” in MERR, Surabaya has partnership with Grab Food to provide Food delivery service for costumer transactions. Electronic Word of Mouth (E-WOM) is a promotional media that has been widely used by the public. The media is able to ease in finding out information about the advantages and disadvantages of products for purchase decision. The study aims to determine the effect of Food delivery service (O2O) and Electronic Word of Mouth (E-WOM) as the simulated variables toward purchase decision in Thai Tea beverage business. The study uses primary data from online questionnaire. The data are taken from thirty customers. Whereas, data collection technique is obtained through questionnaire with 12 statement items. Furthermore, the items are measured using Likert scale of 1 to 5 to know the validity and reliability. The subjects of the study are the costumer who have purchased the beverage onsite or online using Food delivery service (O2O) in Grab Food. Data analysis techniques apply multiple linear regression and partial test to answer the hypothesis. The result indicates that Food delivery service (O2O) does not have positive influence on purchase decision (0.065 > critical significance 0.05). The result of Electronic Word of Mouth (E-WOM) has significant effect on purchase decision (0.045 < critical significance 0.05). The coefficient of determination is 21.7% for Food delivery service (O2O) and Electronic Word of Mouth (E-WOM) toward purchase decision. Whereas, 78.3% is explained by other factors.